Private sector, human resources and health franchising in Africa - Prata Ndola; Montagu Dominic; Jefferys Emma (Bulletin of the World Health Organization, 2005)
In much of the developing world, private health care providers and pharmacies are the most important sources of medicine and medical care and yet these providers are frequently not considered in planning for public health. This paper presents the available evidence, by socioeconomic status, on which strata of society benefit from publicly provided care and which strata use private health care. Using data from The World Bank's Health Nutrition and Population Poverty Thematic Reports on 22 countries in Africa, an assessment was made of the use of public and private health services, by asset quintile groups, for treatment of diarrhoea and acute respiratory infections, proxies for publicly subsidized services. The evidence and theory on using franchise networks to supplement government programmes in the delivery of public health services was assessed. Examples from health franchises in Africa and Asia are provided to illustrate the potential for franchise systems to leverage private providers and so increase delivery-point availability for public-benefit services. We argue that based on the established demand for private medical services in Africa, these providers should be included in future planning on human resources for public health. Having explored the range of systems that have been tested for working with private providers, from contracting to vouchers to behavioural change and provider education, we conclude that franchising has the greatest potential for integration into large-scale programmes in Africa to address critical illnesses of public health importance.